Market timing and statistical arbitrage: Which market timing opportunities arise from equity price busts coinciding with recessions? The Swedish stock market in the financial crises 2008 - Klaus Grobys (Journal of Applied Finance & Banking, 2011)
Even though a random walk process is from a statistical point of view not predictable, some movements can be correlated with specific events concerning other variables. Then, predictable patterns may arise being dependent on this joint event. There is evidence given that equity price busts being associated with recessions continue until the economy switches from the state of recession to an economic pick-up. The following contribution takes into account the Swedish stock index OMX 30 and 25 preselected stocks. The out-of-sample period runs from September 12, 2008 - March 12, 2009, whereas on September 11, 2008 the official press release was issued that European economies face a recession. This study suggests a market timing opportunity resulting in a maximum statistical arbitrage opportunity corresponding to a profit of 19% p.a. with an empirical probability of 50.14%. The optimal defensive strategies, however, exhibit excess returns of 15.12% p.a. above the benchmark with a marginal lower volatility as the benchmark, respectively, 28.08% p.a. with 7.99 percent units higher volatility as the benchmark.
Keywords: C13; C22; G11; G12; 330; statistical arbitrage; financial crises; equity price busts; cointegration